Young motherhood in Singapore : strategies for managing stigma and maintaining positive self-esteem. - Gomes, Gillian Anne. (2013)
The young mother identity is a stigmatized identity in Singapore, and this research illustrates how such negative perceptions that others hold of these individuals affect their sense of self and self-esteem. In this paper, I argue that young mothers do not passively accept such a negative label, but rather, fight against it by adopting impression management, discursive and defensive tactics. In order to mediate and counter the negative effect of stigmatizing labels on these individuals’ self-esteems, young mothers turn to their friends or to social networking sites and mobile applications where their identities are positively-valued and reaffirmed through interactions with other young mothers.